FRASA NOMINAL SUBORDINATIF DALAM 'CERKAK' 'KENDHI WASIYAT' DAN 'SAIRIS SEMANGKA' DI MAJALAH 'PANJEBAR SEMANGAT' - Puti Kharisma Ning (Faculty of Cultures and Languages UIN Raden Mas Said, 2021)
Short story is the story that has a short physical form. Short story is often expressed as story that can be read in one sitting. The storyline is simple and the background includes a limited scope. Short story are written in any languages, such as Javanese. This research was aimed to describe the forms and the grammatical meaning of subordinative nominal phrase that were found on the Javanese short story in Panjebar Semangat magazine published on February 2020. This investigation included two of short stories in this magazine entitled Kendhi Wasiyat and Sairis Semangka, each that represent a story for adult and romance. This study applied descriptive-qualitative method whose data were in the forms of phrases gained from the sentences in the short stories as the data sources. The data were collected by reading and note-taking which were then analyzed by using descriptive method. The results showed that the dominant subordinative nominal phrases (FNS) Â in both short stories was N+N (noun + noun) structure with various Â gramatical meanings. Other existing FNS structure were N+V, N+Adj, Adv+N, and Num+N.